Deformation Potential Constants Ξu and Ξd in n-Si Determined with the Use of the Tensoresistance Effect - Luniov, S.V.; Panasiuk, L.I.; Fedosov, S.A. (Ukrainian Journal of Physics, 2012)
On the basis of longitudinal piezoresistance measurements in the geometry X ║ J ║ [100] and the theory of anisotropic scattering, the deformation potential constants Ξu and Ξd for γ-irradiated n-Si have been determined. It has been shown that, while determining the anisotropy of relaxation times for n-Si with the deep energy level Ec – 0.17 eV, the dependence of the concentration of deep ionized centers on the deformation must be taken into consideration.